Segmental Versus Circumferential Ablation of Pulmonary Veins in Patients with Paroxysmal Atrial Fibrillation - Moustafa Wedn, Ahmed; Eldamaty, Ahmed; Elhalag, Moataz; Elsherif, Rania; Alaasr, Hesham (Open Access Macedonian Journal of Medical Sciences, 2020)
INTRODUCTION: Pulmonary vein isolation (PVI) is the cornerstone of catheter ablation techniques for the treatment of paroxysmal atrial fibrillation (PAF), with significantly improved efficacy compared to antiarrhythmic drugs as shown in CABANA trial. However, the question arises in which PAF patients whether the procedure can be limited to PVs only showing potentials (segmental), or it is really necessary to isolate all PV (circumferential). Even though success rates for circumferential PV ablation (CPVA) have been reported to be higher (up to 90%), than segmental PV ablation, most CPVA procedures previously reported included left atrial linear ablation, additional ablation lesions or lines connecting the mitral valve to the posterior PVs or along the roof of the left atrium which made bias to these studies. AIM: Thus, we initiated this randomized controlled study to evaluate the efficacy of CPVA versus SPVI in subjects undergoing ablation of PAF. METHODS: Our study included 31 consecutive patients who underwent their first radiofrequency ablation for PAF between March 2015 and March 2017. Patients were randomized for circumferential or segmental ablation on the day of the procedure. We had two groups, circumferential (17 patients) and segmental group (14 patients). RESULTS: There was no difference between two groups on our primary endpoint, the recurrence, which was 2 out of 14 patients (14.3%) in the segmental ablation group, compared to 3 out of 17 patients (17.6%) who were circumferential ablated. This difference is statistically insignificant (p = 1). For other endpoints, there was also no statistically significant difference between circumferential and segmental regarding fluoroscopy time, 53.47 ± 8.7 min versus 54.93 ± 15.02 min, p = 0.738, procedure time, 184.18 ±19.28 min versus 191.43 ± 20 min p = 0.315, and even for radio frequency time which was lower in segmental group but did not differ statistically, 35.71 ± 5.73 min versus 34.79 ± 5.29, min p = 0.649. CONCLUSION: The previous studies showed the superiority of circumferential PVI on segmental strategy regarding effectiveness, but in those studies, linear ablations were added to circumferential strategy and done in cases of persistent and PAF. In our randomized study, we compared between two methods in cases of PAF, which showed that segmental ablation is not inferior to circumferential ablation of PVI.